Cobalt - Maaz, Khan (IntechOpen, 2017)
Cobalt is a brittle, hard, silver-grey transition metal with high melting point, hard-wearing at elevated temperatures, good corrosion resistance and improved chemical, magnetic and mechanical properties. This book aims to provide in-depth study and analyses of various synthesis and processing techniques and characterization of cobalt that can lead to its increased applications in recent technology. This book presents deep understanding of the new techniques from basic to the advance level for scientists and engineers. The chapters cover all major aspects about cobalt and its application in material characterization with special emphasis on both theoretical and experimental aspects. This book addresses engineering professionals, students and materials scientists.